Gypenosides improve diabetic cardiomyopathy by inhibiting ROS‐mediated NLRP3 inflammasome activation. Issue 9 (11th July 2018) - Zhang, Hailong; Chen, Xi; Zong, Beibei; Yuan, Hongmin; Wang, Zhizeng; Wei, Yinxiang; Wang, Xuance; Liu, Guangchao; Zhang, Jun; Li, Shulian; Cheng, Guanchang; Wang, Yaohui; et al.
Abstract: NLRP3 inflammasome activation plays an important role in diabetic cardiomyopathy (DCM), which may relate to excessive production of reactive oxygen species (ROS). Gypenosides ( Gps ), the major ingredients of Gynostemma pentaphylla ( Thunb .) Makino, have exerted the properties of anti‐hyperglycaemia and anti‐inflammation, but whether Gps improve myocardial damage and the mechanism remains unclear. Here, we found that high glucose (HG) induced myocardial damage by activating the NLRP3 inflammasome and then promoting IL‐1β and IL‐18 secretion in H9C2 cells and NRVMs. Meanwhile, HG elevated the production of ROS, which was vital to NLRP3 inflammasome activation. Moreover, the ROS activated the NLRP3 inflammasome mainly by cytochrome c influx into the cytoplasm and binding to NLRP3. Inhibition of ROS and cytochrome c dramatically down‐regulated NLRP3 inflammasome activation and improved the cardiomyocyte damage induced by HG, which was also detected in cells treated by Gps . Furthermore, Gps also reduced the levels of the C‐reactive proteins (CRPs), IL‐1β and IL‐18, inhibited NLRP3 inflammasome activation and consequently improved myocardial damage in vivo. These findings provide a mechanism that ROS induced by HG activates the NLRP3 inflammasome by cytochrome c binding to NLRP3 and that Gps may be potential and effective drugs for DCM via the inhibition of ROS‐mediated NLRP3 inflammasome activation.